Faiths, Public Policy and Civil Society - Dinham, A. author. aut Link
XIV, 232 p. 12 illus.
Keywords: This book uses empirical data and theory to explore the role of faiths as public actors; their contribution to welfare services, how they help build community cohesion, and break it down, and what it means for them and for others to be involved in new modes of governance.